Racinaea rufescens (Bromeliaceae), a new species from northern Peru - Treviño-Zevallos, Italo F.; Gouda, Eric J.; Quipuscoa-Silvestre, Victor (Phytotaxa, 2025)
Racinaea rufescens, a new species of Bromeliaceae from montane forests of Rodríguez de Mendoza Province, Amazonas region, northeastern Peru, is described and illustrated. The species is characterized by its small size, once-branched inflorescence with 2–7 laxly arranged spikes, 2.7–5 cm long, strongly reduced floral bracts 2–3 mm long, always shorter than the sepals, and glabrous orange–reddish sepals. Racinaea rufescens has been confused with the related species R. steyermarkii and R. lutheri, but a detailed comparative morphological analysis confirms that it represents a distinct taxon restricted to the Andean-Amazonian transition of northern Peru.